Intrinsic microcrystalline silicon (μc-Si:H) deposited by VHF-GD (very high frequency-glow discharge): a new material for photovoltaics and optoelectronics - Shah, Arvind; Vallat-Sauvain, Evelyne; Torres, P.; Meier, Johannes; Kroll, U.; Hof, Ch.; Droz, C.; Goerlitzer, M.; Wyrsch, Nicolas; Vaněček, M. (My University, 2000)
The development of μc-Si:H technology and the introduction of intrinsic μc-Si:H as photovotaically active material is retraced. Special emphasis is laid on the use of very high frequency glow discharge as a particularly propitious deposition method for μc-Si:H. Thereby, the use of a gas purifier to reduce oxygen content and obtain intrinsic layers with ‘midgap’ character is described. Recent results obtained with single-junction μc-Si:H solar cells and a-Si:H/μc-Si:H tandem solar cells are given. The analysis of carrier collection in single-junction μc-Si:H solar cells is undertaken with the variable intensity measurements method. It yields effective mobility×lifetime (μτ)eff products for the i-layer in p–i–n and n–i–p solar cells in the range 10−7–10−6 cm2 V−1. Similar values have been found for μτ-products in individual layers based on photoconductivity and ambipolar diffusion length measurements. Transmission electron microscopy images for μc-Si:H layers are given. They display a complex microstructure not suspected before. On the other hand, atomic force microscopy data reveal a pronounced surface roughness that correlates well with the optical light scattering and with the pronounced enhancement of the apparent optical absorption coefficient, in the 1–2 eV region, as already observed before.
Keywords: hydrogenated microcrystalline silicon; VHF–GD; photovoltaic; thin-film silicon solar cells; transmission electron microscopy (TEM)